Challenges of employee retention in two Non-Governmental Organisations operating in Zimbabwe - Mutambara, S.; Hungwe, Chipo (Midlands State University, 2014)
The study analyses challenges of retaining employees in non-governmental organisations in an economically distressed environment showing the link between employee commitment and turnover. This is an exploratory qualitative case study. Seventy employees (including 10 former employees who were interviewed through the telephone), from two Non Governmental Organisations (NGOs) participated in this study through questionnaires, Focus Group Discussions (FGDs) and semi-structured interviews. There is a serious problem of retention since 42% of workers would like to leave their organisation given a choice. Workers identified poor labour relations and poorly administered remuneration systems as major causes of dissatisfaction and staff turnover. Workers expected improvement of the labour relations, salaries and staff development programs in order to improve employee retention. Limited funding made it difficult for the two NGOs to provide more secure employment and invest in staff development and motivation and hence retain talent. The research implications are that NGOs should facilitate a learning organisational environment where employees feel valued and receive the necessary support to realise their potential and improve worker commitment. The value of the research is that no known study has been carried out to study employee retention in the non-profit sector in Zimbabwe. The study is exploratory and fills a gap currently existing concerning retention of employees in NGOs.